Digital-based Indonesian Language Learning Strategy in Higher Education : A Systematic Review for 2020-2024 (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze digital-based Indonesian language learning strategies in higher education through a systematic review of articles published between 2020 and 2024. Based on a literature search in Google Scholar, 100 relevant articles were found, of which 84 articles met the inclusion criteria. The analysis results show that the technologies used in Indonesian language learning include ICT, Artificial Intelligence (AI), digital learning media, social media platforms (YouTube, TikTok, Instagram), and interactive applications such as Kahoot and quizzes. Popular learning methods include flipped classroom, Problem-Based Learning (PBL), and Project-Based Learning (PJBL), which support the development of 21st-century skills such as critical thinking, creativity, communication, and collaboration. Furthermore, the COVID-19 pandemic accelerated the adoption of digital learning, which significantly influenced Generation Z students' learning methods. However, limited access to the internet in remote areas remains the main challenge in implementing digital learning. Therefore, improving technology infrastructure and providing training for lecturers to optimize the use of technology in learning, as well as policies that support equitable access to digital education across Indonesia, are essential. This study provides insights for the development of digital-based learning strategies in higher education.